PENGARUH KOMUNIKASI INTERPERSONAL ORANG TUA DAN ANAK TERHADAP PRESTASI BELAJAR ANAK SELAMA MASA SCHOOL FROM HOME (SFH) PANDEMI COVID 19 - Yulia Segarwati; Rasman Sonjaya; Almadina Rakhmaniar (Linimasa : Jurnal Ilmu Komunikasi, 2022)
ABSTRACT This research was motivated by the emergence of anxiety from parents regarding their children's learning achievements, in connection with the necessity to study at home or referred to as School From Home (SFH) due to the covid-19 pandemic. This practically makes school activities must be carried out at home. Education is one of the sectors affected, problems that arise include children who are used to attending lessons at school, as well as socializing with friends and the school environment, now suddenly have to change and change by doing all activities at home with their parents. So far, SFH activities have not been considered effective, considering that there is no mature readiness for parents and children to interact in learning activities like in schools in general, so that learning does not run optimally. The purpose of this study was to obtain data and analyze how much influence parental interpersonal communication has on children's learning achievement during the School From Home (SFH) period of the covid-19 pandemic. The research method used is survey research, with the aim of looking at the effect of the independent variable (variable x) on the dependent variable (variable y), namely parental interpersonal communication on children's learning achievement. Data analysis uses a quantitative approach, through path analysis testing. The results showed that there was a significant influence of Parent and Child Interpersonal Communication on Children's Learning Achievement during the School From Home (SFH) Period of the Covid-19 Pandemic.